Los gramáticos latinos y el acento de enclítica - Castillo Herrera, Marina del (1990)
The enclitic accent is still one of the problems that Classical Philology has to solve. The present paper aims at reviewing once again the testimony of the Ancient Grammar, this time from the point of view of its precedents in the chapter De accentibus of the Grammar until it achieves its final expresion. It can be noticed that, from this perspective, the grammatical testimony provides as well new information or makes more definite the data that it had previously supplied.
Keywords: Lengua latina; Gramática; Filología latina